Infecções bacterianas entéricas e indivíduos infectados pelo vírus da imunodeficiência humana (HIV) - Freitas, Cícero Carlos de; Freitas, Alexandre Gil de (Brazilian Journal of Sexually Transmitted Diseases, 1997)
We review the epidemiology and prevention of and future research priorities for bacterial enteric infections in persons infected with human immunodeficiency virus (HIV). HIVinfected persons are more frequently infecced wich Salmonella, Campylobacter, Listeria and (possibly) Shigella species than are individuais noc infecced with HIV. ln addition, Salmonella and (probably) Campylobacter infections are more like/y to be severe, recurrent, or persistenr and associated with extraintestinal disease when chey occur in HIV-infecced persollS. lnfections caused by Shigella and Vibrio species canais o result in more serious disease in HIV-infected persons rhan in those not infected with HIV. Risk of these infections can be reduced wirh proper precautions, particulary tlrose pertaining to food hygiene, animal concact, and travei. Individuais infecced with HIV should be informed of cheir increased risk oJ accquiring these diseases and should be co1mseled 011 tlu recomended precautions. ln: ANGULO, F.J. & SWERDLOW, D.L. - Bacterial enceric infect ions in prrso~ infected with lwman imunodeficienty virus. Clinical lnfectious Diseases, 21 (Suppl. l):s84-s93, 1993.